2013
DOI: 10.3136/fstr.19.223
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Constituents in Camu-camu Fruit Juice Residue

Abstract: Camu-camu (Myrciaria dubia, Myrtaceae) is a tropical fruit, and is known to be rich in vitamin C. The fruit is mainly used in juice or vinegar production, and large amounts of byproduct, composed of seed and peel, is generated as agricultural and industrial waste. Our studies on camu-camu seed and peel revealed that the seed contains large amounts of polyphenols (400 mg/g). Further studies on the seed resulted in the isolation of vescalagin and castalagin, C-glycosidic ellagitannins with a hexahydroxydiphenoyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…8) Our previous studies investigating the antioxidant activities of camu-camu resulted in the isolation of C-glycosidic ellagitannins, such as castalagin and vescalagin, and their confirmation as the constituents responsible for the antioxidant activities. 9,10) We also previously reported the isolation of rhodomyrtone, an acylphloroglucinol, as a potent antimicrobial constituent in the camu-camu peel. 11) Our successive investigation demonstrated the presence of related antimicrobial acylphloroglucinols, including two new compounds, in the peel and seeds of camu-camu.…”
mentioning
confidence: 93%
“…8) Our previous studies investigating the antioxidant activities of camu-camu resulted in the isolation of C-glycosidic ellagitannins, such as castalagin and vescalagin, and their confirmation as the constituents responsible for the antioxidant activities. 9,10) We also previously reported the isolation of rhodomyrtone, an acylphloroglucinol, as a potent antimicrobial constituent in the camu-camu peel. 11) Our successive investigation demonstrated the presence of related antimicrobial acylphloroglucinols, including two new compounds, in the peel and seeds of camu-camu.…”
mentioning
confidence: 93%
“…At the end of the study, the author concluded that camu-camu showed values of 732 mg GAE/100 g in fresh fruit. Kaneshima et al (2013) state that C-glycosidic elastin, together with ascorbic acid, anthocyanins, cyanidine-3glucoside, total polyphenols, flavonoids quercetin, myricetin, catechin, xarinic acid and the gallic acid of the seeds of the camucamu fruit may be responsible for the antioxidant activity of the fruit. After the analysis and comparison of the antioxidant capacity of other Brazilian fruits, such as acerola, jabuticaba (Plinia cauliflora), cagaita (Stenocalyx dysentericus), açaí (Euterpe oleracea), java plum (Syzygium cumini), camu-camu is highlighted as having a positive correlation between ascorbic acid and total polyphenols in assays that tested the oxygen radical absorbance capacity (ORAC) (r) = 0.…”
Section: Scheme 1 Oxidizing Action Of Flavonoidsmentioning
confidence: 99%
“…In addition to the evidence of antioxidant anti-inflammatory actions of the fruit and its residues, trials and many other supplementary studies have been applied including the use of obese individuals and their comorbidities (Kaneshima et al, 2013;Langley et al, 2015;Arellano-Acuña et al, 2016;Fidelis et al, 2019;Kerimi et al, 2019). This should deserve attention, since many of these diseases reveal a high oxidizing and inflammatory process.…”
Section: Camu-camu (Myrciaria Dubia (Hbk) Mcvaugh) and Immunitymentioning
confidence: 99%
“…Acumula fitoquímicos que son asociados a importantes propiedades (10) . Por ejemplo, fracciones de extractos hidrometanólicos, hidroacetónicos y de extracto crudo de semilla (11) y cáscara de M. dubia, evidenciaron actividad antioxidante debido a sus C-elagitaninos glucosídicos (11,12) . Asimismo, la pulpa mostró altos niveles de ácido ascórbico (AA) y gran cantidad de compuestos fenólicos (13) y también el extracto acuoso de la cubierta de semilla de M. dubia con alto contenido fenólico (14) .…”
Section: Mensajes Clave Introducciónunclassified